(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This paper explores the role, significance, and methodological approaches of the coach in developing volitional qualities in athletes. Willpower is considered a core psychological trait underpinning an athlete’s goal orientation, patience, self-control, and resilience to challenges. The study analyzes pedagogical, psychological, and practical methods used by coaches, including visualization, stress resistance training, competitive exercises, motivation, and discipline. It is demonstrated that these methods effectively help in forming strong willpower in